An evaluation of domiciliary rehabilitation for stroke patients after discharge from hospital - Gladman, John R.F. (1992)
Not only can stroke kill, but it can also disable and handicap the survivors. There is no medical treatment for stroke and not all stroke can be prevented. Rehabilitation, to promote recovery, or maintenance, to support those who do not recover, is required.